Analyses of biomarkers of exposure to nephrotoxic mycotoxins in a cohort of patients with renal tumours - Malir, Frantisek; Louda, Miroslav; Ostry, Vladimir; Toman, Jakub; Ali, Nurshad; Grosse, Yann; Malirova, Eva; Pacovsky, Jaroslav; Pickova, Darina; Brodak, Milos; Pfohl-Leszkowicz, Annie; Degen, Gisela H (Mycotoxin research, 2019)
The Czech Republic occupies the first place in the world in the frequency of renal and other urinary tract tumours, but their aetiology is unknown. To explore whether carcinogenic and nephrotoxic mycotoxins may contribute to kidney diseases in the Czech population, biomarkers of ochratoxin A (OTA) and citrinin (CIT) exposure were determined in biological specimens from a cohort of 50 patients with malignant renal tumours. Biomarker analyses in blood and urine samples used validated targeted methods for measuring OTA and CIT plus dihydrocitrinone (DH-CIT) after enrichment of analytes by specific immunoaffinity clean-up. OTA and CIT plus its metabolite DH-CIT were frequently detected in patient urine samples (OTA 62%; CIT 91%; DH-CIT 100%). The concentration ranges in urine were 1-27.8 ng/L for OTA, 2-87 ng/L for CIT and 2-160 ng/L for DH-CIT. The analyses of blood samples revealed also a frequent co-occurrence of OTA and CIT, in the ranges of 40-870 ng/L serum for OTA and 21-182 ng/L plasma for CIT. This first analysis of biomarkers in blood and urine samples of Czech patients revealed no major differences in comparison with published data for the general healthy Czech and European populations. Nonetheless, a frequent co-occurrence of CIT and OTA biomarkers in patient samples may be of interest with regard to potential interactions with other risk factors for renal disease.
Keywords: nádory ledvin; Ochratoxins; Chromatography, Liquid; Humans; Tandem Mass Spectrometry; lidé středního věku; kohortové studie; Female; Aged; mykotoxiny; dospělí; Mycotoxins; senioři; lidé; Biomarkers; Renal carcinogenicity; ochratoxiny; Ochratoxin A; Cohort Studies; tandemová hmotnostní spektrometrie; citrinin; Adult; Československo; biologické markery; chromatografie kapalinová; ženské pohlaví; Male; Middle Aged; Dihydrocitrinone; Czechoslovakia; Aged, 80 and over; senioři nad 80 let; Citrinin; mužské pohlaví; Kidney Neoplasms